Creative Leadership of School Administrators in the 15th Network Group under the Department of Education, Bangkok Metropolitan Administration - เหล่ากวางโจน, กชกร; รักษนคร, กุลจิรา; คงเที่ยง, สมศักดิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) examine the level of creative leadership among school administrators in Network 15 under the Bangkok Metropolitan Administration. 2) compare the levels of creative leadership of these administrators by gender, age, and educational level and 3) propose guidelines for developing creative leadership for school administrators in Network 15. The sample comprised 201 teachers from schools in Network 15. Data were collected using a five-point Likert questionnaire with item-content validity indices ranging from 0.50-1 and a reliability coefficient of 0.97. Data were analyzed using frequencies and percentages, means, standard deviations, independent-samples t-tests, one-way analysis of variance (F-test) with Scheffé pairwise comparisons, and qualitative content analysis. Findings provide empirical evidence of the current status of creative leadership among the administrators studied and inform recommended strategies for enhancing creative leadership capacity in the network.           Research Findings• Creative leadership of school administrators were at the highest level overall and in all aspects. The highest mean score was teamwork, followed by consideration of individual differences, while vision had the lowest mean score.• Teachers’ opinions did not significantly differ by gender or educational level. However, differences by age were statistically significant at the .05 level.• Guidelines for developing creative leadership include establishing and communicating a shared vision, translating it into measurable and flexible practices, fostering a culture of learning and creativity, recognizing individual differences, and strengthening teamwork through shared goals and open communication.